2022
DOI: 10.1093/jisesa/ieac002
|View full text |Cite
|
Sign up to set email alerts
|

The Life Span and Levels of Oxidative Stress in Foragers Between Feral and Managed Honey Bee Colonies

Abstract: Molecular damage caused by oxidative stress may lead to organismal aging and result in acute mortality to organisms. Thus, oxidative stress resistance and longevity are closely linked. Honey bees (Apis mellifera) are the most important managed pollinator in agriculture, but the long-term survival of honey bees is seriously threatened. Feral honey bee colonies can be used as natural resources to improve honey bee health. One question we ask here is whether feral honey bees are stress resistant or survive longer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Higher oxidative stress (lipid peroxidation) was recorded in feral foragers compared with the managed colonies of honey bees. According to the authors, the outcome suggested a tolerance mechanism rather than a repair mechanism to survive [ 46 ]. Similarly, Li-Byarlay et al [ 47 ] suggested an oxidative stress tolerance in drones (males) experimentally exposed to herbicide methyl viologen, also known as “paraquat”.…”
Section: Discussionmentioning
confidence: 99%
“…Higher oxidative stress (lipid peroxidation) was recorded in feral foragers compared with the managed colonies of honey bees. According to the authors, the outcome suggested a tolerance mechanism rather than a repair mechanism to survive [ 46 ]. Similarly, Li-Byarlay et al [ 47 ] suggested an oxidative stress tolerance in drones (males) experimentally exposed to herbicide methyl viologen, also known as “paraquat”.…”
Section: Discussionmentioning
confidence: 99%